EXPLORING THE MULTIFACETED SPIRITUAL IDENTITIES OF ULU AL-'AZMI FIGURES IN CONTEMPORARY ISLAMIC BOARDING SCHOOLS - Mubarak, Mubarak -; Mujib, Abdul; Rahman Shaleh , Abdul (UIN Antasari Banjarmasin, 2023)
School is an institute that not only develops children's intellect and intelligence, but also teaches emotional intelligence and life skills. Students in boarding schools face various life challenges such as increased academic pressure, social and cultural obligations, financial constraints as well as a rigorous curriculum. This paper aims to explore the strengths and wisdom of Ulul Azmi prophets and apostles so that they can be embedded in the lives of students. This study is based on a descriptive qualitative method using library research. Library research involves the use of literature in the form of books, notes, and research reports from previous studies. Furthermore, this article shows that the values of Ulul 'Azmi include three main dimensions: Firstly, resilience encompasses perseverance in the midst of trials (Dzi Hijr), which indicates the ability to remain strong and resilient in the face of trials and difficulties. Second, steadfastness includes openness to new thoughts and ideas, and winning personality traits that reflect a strong and unyielding attitude in the face of obstacles. Third, perseverance involves the ability to keep trying and not giving up in the face of adversity, with an indicator of strong perseverance being the relentless pursuit of goals. Islamic boarding schools can internalise ulul 'Azmi values through every student's daily activity, which is strengthened by the formation of a sense of responsibility.